Condiciones de trabajo del profesional enfermero, su influencia en la calidad del cuidado en tiempos de Covid-19. Hospital León Becerra. Milagro. noviembre 2020 - marzo 2021 - Paredes Gómez, Aracely Abigail (2021)
Nursing professionals constitute the most important workforce in the health system as care managers, since the beginning of the COVID-19 pandemic they have worked in the first line of care demonstrating quality of care, vocation, commitment and courage to exercise their profession despite the risks, discrimination, deterioration of their physical, mental and emotional health to which they have been exposed. Objective: to identify the working conditions of professional nurses, their influence on the quality of care in times of COVID-19. Methodology Type of study: descriptive, correlational-transversal; population 40 nursing professionals and 40 patients from Hospital León Becerra Camacho, II level of care with referral for COVID-19 patients; Two instruments were applied: Survey "Nursing professional working conditions" with a reliability of Cronbach's Alpha 0.878; the survey “Quality of care” with a reliability of 0.867. Results: 82.5% of nursing professionals have regular working conditions, 17.5% have good working conditions; in quality of care 85% of patients receive very good quality of care, 15% good quality of care; For the correlation of the variables, the Chi Square test was used, obtaining a p-value = 0.677, which indicates that the working conditions of nursing professionals are independent of the quality of care. Conclusion: There is no relationship between the working conditions nursing professional and the quality of care in times of COVID-19. Keywords: quality, working conditions, coronavirus, care managers, patients.